PENGARUH PEMBERIAN BUKU SAKU PANTAU MANDIRI (KUSADARI) TERHADAP PENGETAHUAN DAN KEPATUHAN KONSUMSI TABLET TAMBAH DARAH (TTD) PADA IBU HAMIL - Desi Desi; Tuti Mustika Dewi; Widyana Lakshmi Puspita (Poltekkes Kemenkes Jambi, 2023)
Background: Pregnant women were one of the prone groups to nutritional problems, where during pregnancy the need for iron increased so that they were at high risk of anemia, especially iron deficiency. This happened because the nutritional needs of the mother and fetus increase so that they were at high risk of it. One of the government's efforts in the context of preventing and overcoming iron deficiency anemia and folic acid in pregnant women was to give Blood-Added Tablets (TTD) which were given every day as much as one tablet or a minimum of 90 (ninety) tablets during pregnancy. Methods: This research type was a Quasy Experimental Design with a pretest-posttest design used. The subjects of this study were pregnant women in the first and second trimesters and the number of samples was 35 respondents. Data were taken using a questionnaire and analyzed using univariate analysis and bivariate analysis. Results: There was a difference in the knowledge score at the end of the study before and after education with pocket book media (p = 0.000), while the compliance score at the end of the study showed a difference in compliance before and after education with pocket book media (p = 0.000) Conclusion: There was an effect of providing an independent monitoring pocket book on the knowledge and compliance of the consumption of Blood-Added Tablets (TTD) in pregnant women. Keywords: Pregnant women, pocket book, blood-added tablets, knowledge, compliance to taking Blood-Added Tablets (TTD).